Hazardous Child Labor in Bangladesh: A Critical Evaluation of The Legal and Policy Framework Vis A Vis Practical Challenges (Proceedings of the World Conference on Children and Youth, 2022)
Bangladesh is a signatory of the International Labor Organization’s two landmark conventions on child labor – No.138 on Minimum Age and No. 182 on the Worst Forms of Child Labor. The Bangladesh Labor Act, 2006 prohibits the employment of any child in child labor’s worst forms, including hazardous ones. To eliminate hazardous child labor (HCL) from the country, the government published a list of 38 activities/processes as hazardous to children. However, emerging data suggest that HCL still exists widely in the country, and the COVID-19 pandemic has worsened the situation. The review of existing evidence and relevant reports evinces that the country’s current policies inadequately address the status and remedies of HCL. Based on the author’s desk review, observational experience and visual work, this paper evaluates the competence of the hazardous labor list and current legal protections for children. The findings suggest that lack of implementation, reporting and monitoring opens the floodgate for employers to informally employ children in hazardous work and take advantage of the legal lacunae. Destitute families and street children lack citizenship documents and become easy victims of exploitative employment. The analysis informs that the country’s existing legislative framework and protection policies are critically inadequate to cease HCL in urban areas.
Keywords: hazardous work; child labor; COVID-19 pandemic; Bangladesh